2022
DOI: 10.47616/jamrmhss.v3i3.315
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Vital Lung Capacity on Road Sweeper Workers

Abstract: The decrease level of vital capacity can be restriction, obstruction or both of them. Some factors, like non jobs and environment can lead the decrease level of vital capacity. The goals of this research is knowing all factors that have associated with vital capacity of street sweeper in Kecamatan Medan Denai. The research was conducted on September 2018. The factors of this research are work period, exposure period, mask utilization, employment history, disease history, smoking and sports habits. The total sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…3 In 2005, it was reported that 30% of lung diseases occurred out of a total of 250 million occupational diseases. 4 In 2018, pulmonary disorders entered the 5th position as a disease that causes death. Lung disorders were estimated to increase to 4th place as a disease that causes death in the world by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…3 In 2005, it was reported that 30% of lung diseases occurred out of a total of 250 million occupational diseases. 4 In 2018, pulmonary disorders entered the 5th position as a disease that causes death. Lung disorders were estimated to increase to 4th place as a disease that causes death in the world by 2030.…”
Section: Introductionmentioning
confidence: 99%